The Qur’anic Response to Social Marginalization: A Thematic Analysis of Selected Verses in Surah Al-Baqarah (2:27, 2:154, and 2:187) - Gabriellea Lubaba; Nabil Muhammad Niamillah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study examines the Qur’an’s response to the phenomenon of marginalization through a thematic analysis of QS. Al-Baqarah verses 27, 154, and 187. Using a qualitative approach and library research method, this study analyzes the asbāb al-nuzūl and interpretations of these three verses based on classical and contemporary exegesis books. The findings indicate that these three verses represent the Qur’an’s comprehensive response to various forms of marginalization. QS. Al-Baqarah: 27 criticizes the marginalization of spiritual values through violations of the divine covenant committed by apostate, hypocrite, and people of the book groups; QS. Al-Baqarah: 154 performs an epistemological deconstruction of the marginalization of martyrs through redefining the concepts of life and death; while QS. Al-Baqarah: 187 offers a rukhṣah mechanism as a response to marginalization through laws that do not consider human anthropological limitations. These three verses form a tripartite conceptual framework that complement each other in the construction of a civil society (madani society), emphasizing the importance of spiritual commitment, appreciation for sacrifice, and balance in law implementation. This study concludes that the Qur’an offers an integral paradigm in addressing marginalization through an approach that is simultaneously firm and relevant for contextualization in answering contemporary societal challenges.